Tableware and food consumption: Tableware and food consumption - Jung, Eun Young; Park, Eun Young (Progress in Nutrition, 2021)
We conducted a review to investigate whether the evidence for an association between tableware in the built food environment and food consumption is consistent and important. We systematically searched electronic databases for articles published in English since 2000. A total of 541 studies were identified. Of these, we excluded 525 studies and reviewed 16. The types of tableware studied were plates (n=7), bowls (n=5), glasses (n=2), cups (n=1), spoons (n=1), and chopsticks (n=1). Their manipulated properties were size (n=9), color (n=6), shape (n=5), and type (n=1). In conclusion, there is a tendency to use tableware as an indication of how much should be served and consumed. Simply using smaller tableware might be all that is required to make an environment less conducive to overeating. One possible effect of tableware color has been identified in this review. Thus, the review demonstrates that tableware affects mainly visual aspects of perception.